Forthcoming hyperfluorescence display technology: relevant factors to achieve high-performance stable organic light emitting diodes - Gawale, Yogesh; Ansari, Rasheeda; Naveen, Kenkera Rayappa; Kwon, Jang Hyuk (Frontiers in Chemistry, 2023)
Over the decade, there have been developments in purely organic thermally activated delayed fluorescent (TADF) materials for organic light-emitting diodes (OLEDs). However, achieving narrow full width at half maximum (FWHM) and high external quantum efficiency (EQE) is crucial for real display industries. To overcome these hurdles, hyperfluorescence (HF) technology was proposed for next-generation OLEDs. In this technology, the TADF material was considered a sensitizing host, the so-called TADF sensitized host (TSH), for use of triplet excitons via the reverse intersystem crossing (RISC) pathway. Since most of the TADF materials show bipolar characteristics, electrically generated singlet and triplet exciton energies can be transported to the final fluorescent emitter (FE) through Förster resonance energy transfer (FRET) rather than Dexter energy transfer (DET). This mechanism is possible from the S1 state of the TSH to the S1 state of the final fluorescent dopant (FD) as a long-range energy transfer. Considering this, some reports are available based on hyperfluorescence OLEDs, but the detailed analysis for highly efficient and stable devices for commercialization was unclear. So herein, we reviewed the relevant factors based on recent advancements to build a highly efficient and stable hyperfluorescence system. The factors include an energy transfer mechanism based on spectral overlapping, TSH requirements, electroluminescence study based on exciplex and polarity system, shielding effect, DET suppression, and FD orientation. Furthermore, the outlook and future positives with new directions were discussed to build high-performance OLEDs.